Common Content Knowledge manifested by a teacher in teaching basic concepts of functions: A case study - Rodríguez-Flores, Ariana (2016)
This article presents a case study based on the common knowledge of the content in mathematics shown by a professor when teaching basic function concepts in a daytime academic high-school in Costa Rica. It is based on research regarding the mathematics knowledge required for teaching, which is a booming research area in faculty training. The educational analysis is used as a tool to identify and characterize this knowledge. We recognize that the professor shows significant knowledge of mathematical concepts, appropriate procedural knowledge and valuable ability to define conceptual structures. Furthermore, this knowledge relates to knowing about the study program for high-school education, indicators which intertwine with the educational knowledge of the content.